Augmented Reality as Learning Medium for Preservation of Traditional Musical Instruments in Bangka - Juniawan, Fransiskus Panca; Sylfania, Dwi Yuny (Politeknik Elektronika Negeri Surabaya (PENS), 2019)
Nowadays the use of technology is something that can be found anywhere. This condition has an impact on the loss of awareness of the Indonesian cultural treasures value in the form of traditional tools. No exception to traditional musical instruments on Bangka Island which began to lose its popularity. At present, most teenagers on Bangka Island cannot play traditional musical instruments. Likewise with the children who do not know and not even know their own regional musical instruments. With the continuation of this condition, it is feared that the existence of traditional Bangka musical instruments will disappear, as well as human resources that can play it. Augmented Reality (AR) is a visual technology that can display objects in 3D. The advantage of this technology is being able to give a display of real-time musical instrument in the form of dynamic 3D visualization of objects and it is in accordance with the movements of the user's smartphone camera. AR has also been applied in various cases as a solution to problem-solving. Therefore, to overcome this problem, an application to preserve the traditional Bangka musical instruments using Augmented Reality (AR) is forming. The 3D objects of musical instruments are made using Maya. Unity is also used as an engine for the application of 3D modeling on the Android system, and Vuforia SDK as it’s augmented reality engine. The results of performance testing obtained 100% running well. From the results of testing the user experience with the HARUS method, it is proven that the system has comprehensibility aspects of 75.98% and manipulability aspects of 80.74% so that the total value HARUS be 78.36%.